Endoscopic Administration of Mesenchymal Stromal Cells Reduces Inflammation in Experimental Colitis. Issue 8 (22nd May 2018) - Barnhoorn, Marieke; de Jonge-Muller, Eveline; Molendijk, Ilse; van Gulijk, Mandy; Lebbink, Oscar; Janson, Stef; Schoonderwoerd, Mark; van der Helm, Danny; van der Meulen-de Jong, Andrea; Hawinkels, Lukas; Verspaget, Hein
Abstract: Background: Mesenchymal stromal cells (MSCs) are a potential therapeutic modality in inflammatory bowel diseases (IBDs) because of their immunomodulatory and regenerative properties. However, when injected systemically, only a small portion of the cells, if any, reach the inflamed colon. In this study, we assessed whether endoscopic injections of MSCs into the intestinal wall of the inflamed colon affect the course of experimental colitis. Furthermore, we investigated if injection of aggregated MSCs in spheroids could enhance their therapeutic ability. Methods: Expression levels of in vivo MSC aggregates and in vitro MSC spheroids were compared with monolayer cultured MSCs for both anti-inflammatory and pro-regenerative factors. Subsequently, MSCs and MSC spheroids were injected endoscopically in mice with established dextran sulfate sodium (DSS)–induced colitis. Results: Endoscopically injected MSCs and MSC spheroids both alleviated DSS-induced colitis. Furthermore, both in vivo and in vitro MSC spheroids showed increased expression of factors important for immunomodulation and tissue repair, compared with monolayer cultured MSCs. Despite differential expression of these factors, MSC spheroids showed similar clinical efficacy in vivo as single-cell suspension MSCs. Analysis of serum samples and colon homogenates showed that local MSC therapy resulted in increased levels of interferon-γ, indoleamine 2, 3-dixoygenase, and interleukin-10. Conclusions: Endoscopic injections of MSCs and MSC spheroids in the inflamed colon attenuate DSS-induced colitis. Our data show that endoscopic injection can be a feasible and effective novel application route for MSC therapy in patients with luminal IBD.